1998
DOI: 10.1159/000021444
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Prosodic Characteristics of the Speech of People with Parkinson’s Disease and Friedreich’s Ataxia with Neurologically Normal Speakers

Abstract: The realization of prosody (speech rate, fundamental frequency, intonation) was investigated in a group of 10 individuals with Parkinson’s disease and a group of 10 individuals with Friedreich’s ataxia. Data from these two neurologically disordered groups were compared to individuals without neurological impairment. Both neurologically impaired groups retained some aspects of normal speech prosody, while other aspects were affected to a significant degree. The prosodic characteristics of speakers with Parkinso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…A decrease in F 0 range during tasks was also reported by other investigators (Flint, Black, Campbell-Taylor, Gailey, & Levinton, 1992;Goberman, Coelho, & Robb, 2005;Metter & Hanson, 1986). Acoustic investigations of statements and questions produced by normal speakers and PD patients also demonstrated decreased F 0 changes marking the differences between the declarative and interrogative modes (Le Dorze, Ouellet, & Ryalls, 1994;Le Dorze, Ryalls, Brassard, Boulanger, & Ratte, 1988;Torp & Hammen, 2000). More recently, in an acoustic investigation of PD speech and control speech in linguistic and emotional context, F 0 differed between the two speaker groups for contrastive stress and emotional prosody production (Cheang & Pell, 2007).…”
Section: Prosodic Aspects Of Patients With Pdsupporting
confidence: 73%
“…A decrease in F 0 range during tasks was also reported by other investigators (Flint, Black, Campbell-Taylor, Gailey, & Levinton, 1992;Goberman, Coelho, & Robb, 2005;Metter & Hanson, 1986). Acoustic investigations of statements and questions produced by normal speakers and PD patients also demonstrated decreased F 0 changes marking the differences between the declarative and interrogative modes (Le Dorze, Ouellet, & Ryalls, 1994;Le Dorze, Ryalls, Brassard, Boulanger, & Ratte, 1988;Torp & Hammen, 2000). More recently, in an acoustic investigation of PD speech and control speech in linguistic and emotional context, F 0 differed between the two speaker groups for contrastive stress and emotional prosody production (Cheang & Pell, 2007).…”
Section: Prosodic Aspects Of Patients With Pdsupporting
confidence: 73%
“…Previous research has shown, in fact, that speakers with PD are impaired in specific aspects of intonation, such as the use of pitch patterns to mark contrastive stress and to indicate the sentence mode (Blonder, Gur, & Gur, 1989; Cheang & Pell, 2007; LeDorze, Ryalls, Brassard, Boulanger, & Ratté, 1998). Deficits in other areas, such as the strength and placement of focus markers and the production of phonemic stress patterns, appear to be more variable (Cheang & Pell, 2007; Darkins, Fromkin, & Benson, 1988; Hertrich & Ackermann, 1993; Penner, Miller, Hertrich, Ackermann, & Schumm, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although dysarthria is pervasive in FA, the exact neurologic components have been less well defined 4–9. Most speech dysfunction in FA reflects articulation deficits and is frequently classed with apraxic speech in that no true aphasia is present.…”
mentioning
confidence: 99%